Studies Conducted in Turkiye Against Armenian Claims/Ermeni Iddialari Karsisinda Turkiye'de Yapilan Calismalar - Karacakaya, Recep (Tarih dergisi, 2023)
Armenians have taken on great propaganda activities since the 1920s to prove that they have been subjected to a genocide. They have written many boks, published many articles in scientific journals, and continue to do so. While only Armenians initially produced works on the subject, researchers from many different countries around the world are seen to have recently begun writing on the subject.